Edukasi Kesehatan Terhadap Tingkat Pengetahuan Tentang Leukimia pada Pelajar di SMAN 5 Cimahi - Theophylia Melisa Manumara; Andhika Rafi Ramadhan; Raisya Aoliya Somantry; Septia Putri Hartanti; Shofiyani Khoirotul Millah; Desi Novitasari; Nadziah Mar'atush Sholihah; Turindah Turindah; Jum'ati Jum'ati (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The topic of leukemia was raised in this health education activity because this disease is a serious blood cancer that has a major impact on society. Education on prevention and understanding of the disease is considered important. Leukemia is described as a disorder caused by the proliferation of immature white blood cells that arise due to genetic abnormalities in hematopoietic cells, and is influenced by exposure to radiation, chemicals, viral infections, immune disorders, and genetic factors. Based on WHO Globocan 2025 data, there were 487,294 new cases and 305,405 deaths worldwide, with a prevalence of 17.42 per 100,000 population. In Indonesia, this disease ranks 10th as the cancer with the highest incidence and mortality rates, while Lampung Province recorded 214 inpatient cases in 2015. This information shows the need for increased public education. In implementing this health education program, a post-test design was used to assess changes in understanding after the material was presented. The presentation was delivered through a presentation, and participants' knowledge was then measured using a quiz. Students in class XII-8 at SMAN 5 Cimahi were designated as the target group. The evaluation results showed that there was an increase in understanding after the presentation and quiz methods were applied. The low level of student participation was one of the limitations of the activity. Overall, these results show that interactive educational approaches can support improvements in health literacy.